Individual and Job Characteristics as Predictors of Employee Job Satisfaction: Evidence from Samsat Makassar I Selatan - Nurhasni Muis (LPPM STIEM, 2025)
: This study aims to examine the influence of individual characteristics and job characteristics on employee job satisfaction at Samsat UPT Pendapatan Wilayah Makassar I Selatan. The research is grounded in the growing need to improve public service quality, which is strongly shaped by employees’ psychological conditions and perceptions of their work. A total of 83 employees participated as respondents, selected through a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression. The findings reveal that individual characteristics have a positive and significant effect on job satisfaction, indicated by a t-value of 3.348 and a significance level of 0.001. This demonstrates that differences in employee abilities, personality traits, experiences, and work orientation substantially contribute to their job satisfaction. Additionally, job characteristics show a positive and significant effect, with a t-value of 2.667 and a significance level of 0.010, indicating that task variety, autonomy, feedback, and job significance play an important role in enhancing satisfaction. Collectively, both variables contribute 43.2% to the variation in job satisfaction. These results highlight the importance of person–job fit–based human resource management and improvements in job design to build a more productive, harmonious, and high-performing work environment within public service organizations.